Blood-brain barrier disruption: mechanistic links between Western diet consumption and dementia - Hsu, Ted M.; Kanoski, Scott E. (Frontiers in Aging Neuroscience, 2014)
Both obesity and Alzheimer’s disease are major health burdens in Western societies. While commonly viewed as having separate etiologies, this review highlights data suggesting that intake of “Western diets”, diets high in saturated fatty acids and simple carbohydrates, may pose a common environmental risk factor contributing to the development of both of these adverse pathologies. We discuss the effects of Western Diet intake on learning and memory processes that are dependent on the hippocampus, as well as the importance of this brain region in both obesity development and the onset of Alzheimer’s and other dementias. A putative mechanism is discussed that mechanistically links Western diet consumption, blood brain barrier degradation, and subsequent hippocampal damage and dementia pathology.